1991
DOI: 10.1007/bf02356996
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of bovine campylobacteriosis in indigenous cattle of three states in Nigeria

Abstract: A survey of bovine campylobacteriosis in breeding bulls and cows was carried out in the states of Kaduna, Kano and Borno. Six hundred and eighty nine cattle composed of 585 and 104 breeding bulls and cows respectively were sampled. Campylobacter fetus subsp. venerealis was isolated from 12 bulls while Campylobacter fetus subsp. fetus was isolated from three of them. Campylobacter fetus subsp. fetus was isolated from four cows while Campylobacter fetus subsp. veneralis was isolated from one cow. The overall pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 2 publications
2
11
0
Order By: Relevance
“…Of the two subspecies of C. fetus , C. f. venerealis was more common, which is in agreement with other studies [2,4,8]. It is noteworthy that C. f. venerealis is more pathogenic than C. f. fetus [10,41].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Of the two subspecies of C. fetus , C. f. venerealis was more common, which is in agreement with other studies [2,4,8]. It is noteworthy that C. f. venerealis is more pathogenic than C. f. fetus [10,41].…”
Section: Discussionsupporting
confidence: 91%
“…However, it is evident from the result of this study that C. fetus is common in northern Nigeria and may be an important cause of infertility. A similar study performed in Nigeria 20 years ago reported a lower prevalence of 2.9% of cattle and 20% of herds [4]. Although the authors sampled both bulls and cows, the herd-level prevalence was comparable to our study; however, the animal-level prevalence was lower, suggesting that there has been an increase in the prevalence of this disease.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…They result in huge economic losses due to abortion, repeat breeding, decrease in number of calves, culling and replacing affected animals and decreased milk production due to clinical mastitis [3,13,19-22]. In contrast, studies of trichomonosis in Nigeria have revealed a low or zero prevalence [23-25].…”
Section: Introductionmentioning
confidence: 99%